(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
In childhood diseases, the varicella (chickenpox) and measles diseases considered an important condition. In this research we have designed and implemented an expert knowledge-based system utilizing IOT for early diagnosis of these diseases for children in kindergarten. The system was developed according to an object-oriented software engineering paradigm using UML tools. Also it developed based specific roles in web domain using IoT environment. Furthermore the system able to send a message contains all details on the infection type and description on the disease to the parents. This system can be used by kindergartens or parents as a domestic application for early diagnosis of the disease through the symptoms that appear on the affected child. The knowledge – based system was implemented using python 3.8. The results observe a significant response for detecting and diagnosis the Varicella (Chickenpox) and Measles diseases.